MSME Busines Performance: The Role of Competitive Advantage, Supply Chain Management Practices and Innovation - Muthia Roza Linda; Rida Rahim; Suhery Suhery; Thesa Alif Ravelby; Riza Yonita (Universitas Muhammadiyah Jakarta, 2022)
Good business performance for every business actor is a major concern to ensure the competitiveness and sustainability of the company. To be able to achieve satisfactory business performance, MSMEs must be able to carry out various strategies such as creating competitive advantage, implementing SCM Practices, and innovate. This study was conducted to see how MSME supply chain management practices, competitive advantage, and innovation affect the Business Performance of Snack MSMEs in Padang City. The population of this research is snack food SMEs assisted by the Department of Trade, Cooperatives, and SMEs of Padang City, with a total sample of 130 SMEs. Research data were collected using a questionnaire. The data that has been collected was analyzed using a multiple regression analysis approach with SPSS ver software. 24. The results show that (1) competitive advantage has a significant effect on business performance, (2) SCM Practicessignificant effect on business performance, and (3) innovation has no significant effect on business performance. In Padang City snack SMEs, competitive advantage, SCM Practices and innovation have an influence of 87.7% on MSME business performance.